KINERJA PEMASARAN : PERCAYA TAKHAYUL DENGAN NAMA BISNIS - Gazali, Immanuel; Adek, Adek; Suryadiputra, Siska (Jurnal Ilmu Manajemen, 2019)
This study aims to determine the existence of a significant influence between takahyul on business names; there is a significant influence between business names on marketing performance; there is a significant influence between superstition on marketing performance; and the existence of a significant influence of superstition influences marketing performance by moderating business names.This type of research uses quantitative and descriptive, the aim is to provide or describe a situation or phenomenon that is happening now by using scientific procedures to answer the problem in actual terms. The population is a business name superstitious trust entrepreneur. The total sample of 200 respondents was taken by purposive sampling technique. The data collection method uses a questionnaire. The sample analysis method uses purpose sampling with business criteria having a business name and extending the business name in front of its business location and having an average turnover from 0 to Rp. 3,000,000. per day.The results of this study are that there is a significant influence of business name variables on marketing performance, except superstition on marketing performance